Comparative study between readjustable gastric balloon filled with air and others filled with saline inserted for obese patients and their effect on weight loss - Ibrahim, Ahmed Abdel Monem (International Surgery Journal, 2017)
Background: Gastric balloon is widely used nowadays for weight loss for a category of patients that need loss of weight with average from 15 to 40 kgs and there is a long time of revolution for design and construction of gastric balloon beginning from non-inflatable air filled to re-inflatable saline filled ones.1 The gastric balloon we used in our study is the re-inflatable saline filled type which formed from very tough type of elastic material resist gastric acidity for long as more than one year,2 and the advice period for insertion ranging from 6 months to one year before removal.3 Aim was to compare the effect of filled material that we inject inside the balloon either air or saline on the reduction of weight of patients at the end of one year insertion of the re-inflatable gastric balloon. Methods: Thirty obese patients (19 female) and (11 male) undergoing gastric balloon insertion at Alsalama hospital Abu Dhabi are classified into two groups (group I) 15 patients (9 female and 6 males) are subjected to insertion of re-inflatable gastric balloon filled with 700 ml air and (group II) 15 patients (10 female and 5 male) are subjected to the insertion of re-inflatable gastric balloon filled with saline mixed with methylene blue and both groups was followed at 2,4 and 12 months postoperative. Results: The use of gastric balloon filled with saline causes more weight loss in patients than re-inflatable gastric balloon filled with air at the end of study. Conclusions: The use of saline filled re-inflatable gastric balloon insertion for weight reduction gives more good results in reduction of patient’s weight in our study.